The use of the Google Forms as an assessment tool in the teaching and learning process in times of the Covid-19 pandemic: A study in a basic education school (Research, Society and Development, 2021)
The research: The use of Google Forms as an assessment tool in the teaching and learning process in times of Covid-19 pandemic, showed a descriptive, cross-sectional study carried out with high school students from a public school in the city of Belém do Pará , in view of the use of Google forms, as an assessment tool carried out from April 1, 2020 to January 15, 2021. There was a significant increase in the use of technological tools used in education in order to supply educational and support educational establishments in all spheres of education. The proposal to use Google Forms as an evaluation tool has become an indispensable tool, but some restrictions have been found. The objective of the present study is to describe the use of the google forms tool as an assessment tool with students of basic education in times of pandemic of the covid-19. Problems were observed that affect educational development, such as mental health and inequality due to the lack of access to the technological means necessary to maintain education in addition to the social vulnerability faced by countless students.